The roots of gender bias: misogynist hadiths in pesantrens - Marhumah Marhumah (Indonesian Journal of Islam and Muslim Societies, 2015)
Women are regarded as “the second class” by some people in pesantrens. Thisknowledge has rooted in hadiths cited in the books studied and implementedin many pesantrens. To counteract  this  tendency,  it  is  therefore  important  touse  a  feminist  approach  to  review  and  criticize  the books which  can  also beused  to understand and  solve  the problems of mis-interpretation of  religioustexts. The misogynist hadiths have been widely circulated and taught in pesantrenunder  the authority of Kyai  (male  religious  clerics) and nyai  (female  religiouscleric) who  have  the  authority  to  decide which  hadiths  are  allowed  to  betaught and socialized in religious teachings and sermons. This is because manyteachers emphasize the importance of preserving tradition and religious normsdisegarding gender bias. Some feminist activists have tried to reform the mindsetsof pesantren leaders both male and female by changing the authoritarian modelof  leadership  to  a  democractic  one. To  do  this, new  historical,  sociologicaland anthropological approaches are required to re-interpret and contextualizemisogynist  hadiths.Perempuan  dianggap  sebagai warga  “kelas  dua”  dalam  beberapa  kitab  yangdiajarkan di pesantren. Pengetahuan ini memiliki akar yang kuat dalam hadith-hadith  yang  dikutip  dalam  buku-buku  yang  diajarkan  di  pesantren. Untuk melawan  arus  kecenderungan  ini,  penting  untuk menggunakan  pendekatanfeminis  dengan meninjau  kembali  dan mengkritik  kitab-kitab  tersebut.Pendekatan ini dapat digunakan sebagai cara untuk memahami dan menyelesai-kan masalah kesalahan tafsir pada teks teks keagamaan. Hadith-hadits misoginis(membenci perempuan) diajarkan secara luas di pesantren di bawah wewenangPak Kyai  atau  Ibu Nyai  yang menentukan  kitab-kitab mana  yang  boleh  dandilarang di pesantren. Para guru tersebut lebih mementingkan menjaga tradisidan norma-norma agama yang seringkali bias jender. Beberapa aktivis feministelah mencoba mereformasi  pola  pikir  para  pengasuh  pesantren  baik  lakimaupun perempuan dari kepemimpinan yang otoriter ke kepemimpinan yangdemokratis. Untuk  itu,  pendekatan-pendekatan  historis,  sosiologis  danantropologis  yang  baru  diperlukan  guna memahami  ulang  hadith-hadithmisoginis  tersebut.